RESPONS PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) TERHADAP PEMBERIAN VERMIKOMPOS DAN URINE KELINCI - Anita Lydia Beta Simamora; Toga Simanungkalit; Jonis Ginting (Jurnal Agroekoteknologi, 2015)
ABSTRACTResponse in Growth and Yield of Shallot (Allium ascalonicum L.) on Giving Vermicompost andRabbit Urine. The use of chemical fertilizersis an alternative that is often selected farmers toincrease the production of shallot. Because of that giving of vermicompost and rabbit urine is expectedto replace the role of chemical fertilizers in increasing the growth and production of shallot. Thisresearch had been conducted at Farm Resident on street Pasar I number 89 Tanjung Sari, Medanfrom May until July 2013 using factorial randomized block design with two factor, i.e. dose ofvermicompost (0, 15, 30 and 45 g vermicompost/plant) and dose of rabbit urine (0, 125 and 250 cc/l).Parameter observed were plant height, tillers number per clump, leaves number per clump, clovenumber per sample, wet weight tuber per sample, wet weight tuber per plot, dry weight tuber persample, and dry weight tuber per plot. The result showed that vermicompost treatment not significantlyaffected all of parameter observed. Rabbit urine treatment increase plant height, tillers number perclump, clove number per sample, wet weight tuber per sample, wet weight tuber per plot, dry weighttuber per sample, and dry weight tuber per plot. The treatment interaction significantly effected onparameters tillers number per clump and clove number per sample. The best result were showed byvermicompost treatment 15 g/plant and rabbit urine treatment 250 cc/l.Keywords : Vermicompost, rabbit urine, shallot